2008
DOI: 10.1109/jmems.2008.2004786
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium-Based Multimetal-Contact RF MEMS Switch With a Corrugated Diaphragm

Abstract: This paper presents a ruthenium metal-contact RF microelectromechanical system switch based on a corrugated silicon oxide/silicon nitride diaphragm. The corrugations are designed to substantially reduce the influence of the fabricationinduced stress in the membrane, resulting in a highly insensitive design to process parameter variations. Furthermore, a novel multilayer metal-contact concept, comprising a 50-nm chromium/ 50-nm ruthenium/500-nm gold/50-nm ruthenium structure, is introduced to improve the contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Soft metals, such as gold, are suitable for reducing contact resistance, but their contact surfaces are prone to microwelding. Ke et al [58] coated Au contacts with Ru to investigate placing harder materials on top of softer materials for a lifetime enhancement. Yang et al [59] showed Au-Ni alloy contacts resist material transfer better than Au-Au contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Soft metals, such as gold, are suitable for reducing contact resistance, but their contact surfaces are prone to microwelding. Ke et al [58] coated Au contacts with Ru to investigate placing harder materials on top of softer materials for a lifetime enhancement. Yang et al [59] showed Au-Ni alloy contacts resist material transfer better than Au-Au contacts.…”
Section: Introductionmentioning
confidence: 99%
“…CDs have been studied for quite a long time and were first widely used in capacitive pressure sensors and RF MEMS switches [41,42,[44][45][46][52][53][54][55][56]. Introducing the corrugated structure into the fiber-optic sensor can significantly improve the performance of sensors.…”
Section: The Application Of Cds In Miniature Fiber-optic Pressure Senmentioning
confidence: 99%
“…A solution to this problem is the use of RF-MEMS switched capacitors to obtain precise frequency shifts (Pothier et al 2005;Nadaud et al 2016). The fabrication residual stress can be reduced either by improving the geometry and the structural switch design (Mahameed et al 2010;Philippine et al 2013;Patel et al 2012;Zaireie et al 2013;Yang et al 2015), since these determine their stiffness and therefore actuation voltage and reliability, or utilizing particular materials, and therefore a special dedicated fabrication process (Palego et al 2009, Ke et al 2013, Sterner et al 2008. In (Patel et al 2012) a crab-leg beam geometry is used to achieve a highly reliable switch, but with a high actuation voltage (80-90 V).…”
Section: Introductionmentioning
confidence: 99%